The Reconstruction of a fourteenth-century façade of the Theutonic House ('Het Duitse Huis') in Utrecht (Bulletin KNOB, 2005)
The medieval cloister complex the Theutonic House in Utrecht is situated on the west side of Springweg. From 1811 to 1990 a Military Hospital was established here. The basic principle of the restoration, which was started in 1993, was that the eastern gable of the 14th-century main building had to be restored.The information still available in the building itself made a reconstruction without guesswork possible, although the central government was not in favour of it. However, architect Aart Oosting decided to restore the fourteenth-century form, also because the articulation of the brickwork of the upper floor left little room for inventing something explicitly new that was not artificial.The effect of the new façade with its large staircases and daylight access for the upper-floor space, extending up to the roof, is completely in line with the wish to create a hall of great architectonic character. It was expressly decided, however, to paint the external plaster of the facade white, in harmony with the 'empire' finishing of the southern facade and the facades of the former dwelling of the land commanders.The light openings of the windows on the upper floor and the new windows on the ground floor obtained modern glazing. In this case the decisions in the scope of the restoration are the result of intensive building-historical research and a substantial contribution of the researcher during the many building meetings.